Sediment distribution and littoral drift direction for the coastline between Batu Rakit and Setiu, Terengganu - Mohd Azam Mat Yaacob (Institut Oseanografi, 2012)
The main objective o f this study is to determine the sediment distribution and investigate the net littoral drift direction from Batu Rakit to Kuala Setiu. The study is very important as a preliminary study to any coastal zone management decisions.